2022
DOI: 10.48550/arxiv.2211.00333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Derivation of $\mathcal{PT}$-symmetric Sine-Gordon model and its relevance to non-equilibrium

Abstract: The Parity-Time PT -symmetric non-Hermitian Sine-Gordon(nhSG) model derived from the nonequilibrium spin-boson model. We have derived the Keldysh rotation for spin operators, from which the SG model can be derived. We perform renormalization group calculations in the Keldysh fields and compare the fixed points and the flow of the effective couplings of nonequilibrium and non-Hermitian models. Also, we explicitly find the self-energies and compare the two methods to understand the regimes where PT symmetry pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the above solution, F is an incomplete elliptic function of the first kind, and E is an elliptic function of the second kind. P and T are polynomial and transcendental functions, respectively.Similar elliptic functions are found to solve nonhermitian problem [34] to connect the nonequilibrium self-energy of an open system. The inset graph shows the non-interacting FP we got when we set either JY or K to negative otherwise, we have two impurities Kondo effect, where all couplings diverge.…”
Section: Appendix F: Impurity Transport Calculationmentioning
confidence: 90%
See 1 more Smart Citation
“…In the above solution, F is an incomplete elliptic function of the first kind, and E is an elliptic function of the second kind. P and T are polynomial and transcendental functions, respectively.Similar elliptic functions are found to solve nonhermitian problem [34] to connect the nonequilibrium self-energy of an open system. The inset graph shows the non-interacting FP we got when we set either JY or K to negative otherwise, we have two impurities Kondo effect, where all couplings diverge.…”
Section: Appendix F: Impurity Transport Calculationmentioning
confidence: 90%
“…Moreover, adding second-order self-energy to the original Hamiltonian leads to non-Hermitian physics [32]. In open systems, adding finite-order self-energies can also give rise to effective non-Hermitian models [33][34][35]. In a theoretical study, it has been shown that complex solutions emerge from various types of potentials and their symmetries [36].…”
Section: Emergence Of Complex Solutionmentioning
confidence: 99%